READING SELF-EFFICACY AND WRITING SELF-EFFICACY IN ENGLISH STUDENT TEACHERS’ PAPER WRITING (RETAIN, 2020)
AbstractThe primacy of self-efficacy as an independent contributor to task performance of language skills such as reading and writing has been widely recognized. Considerable amount of studies has also found self-efficacy as predictive toward academic achievement of the aforementioned language skills. The interplay of self-efficacy in academic reading and writing skills of English student teachers delves into the tenet of literacy skill which puts reading as an antecedent of writing. The present study thus attempts to explain; 1) the way reading self-efficacy is portrayed by reading achievement in Extensive Reading, 2) the way writing self-efficacy is portrayed by writing achievement in Paper Writing and 3) how reading self-efficacy facilitates English student teachers’ paper construction. The objectives of the present study are set upon the aforementioned focuses. Methodology used in this study includes sequential explanatory as the design and thus has both quantitative and qualitative phases in each part. Positive moderate correlation was found among self-efficacy in academic reading and self-efficacy in academic writing (ρ=0,612, n=38, p=0.05). While both reading and writing self-efficacies were found insignificantly correlating subject’s achievements in respective courses, plausible findings gained from exploratory factor analysis (EFA) that was further triangulated by content analysis of selected participants’ conceptual papers as well as thematic analysis of their answers in semi-structured interviews provide possible explanation to the results of quantitative phase.Keywords: Reading Self-efficacy, Writing Self-efficacy, Academic Achievement